URGENSI PEMIDANAAN TERHADAP KORPORASI SEBAGAI PELAKU TINDAK PIDANA - Ratri Novita Erdianti (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2015)
Indonesia has admitted the corporation as criminals, this can be evidenced by the corporate setting as criminals in various laws and regulations in Indonesia outside KUHP.Akan However, although there has been a recognition that the corporation is the subject of criminal law, but in reality we not see that there are many criminal acts involving the corporation that is not directing the corporation to serve as a suspect in the judicial process. It would be a problematic for the enforcement of criminal law in Indonesia.Dengan the recognition of the corporation as the subject of a criminal act, then it is important to criminalize not only the board but also to related corporations. With no corporate dipidananya who committed the crime, then the purpose of punishment will be different if the criminal is only addressed to administrators but not to the corporation. In general, dropped criminal purpose is other than the deterrent effect against the corporation who committed the crime, but also as an effort to prevent the criminal act is not performed by the other corporations. Associated with a given criminal purposes, if only the criminal responsibility on the corporate board of sentencing objectives to be achieved will be difficult to achieve. It would be important to not only penalize the corporate board, but also still penalize the corporation concerned.